TEACHING COMPUTER GRAPHICS ON THE BASIS OF MODERN METHODS AS A PEDAGOGICAL PROBLEM IN THE CONDITIONS OF DIGITAL EDUCATION (World Bulletin of Management and Law, 2023)
This article provides information on the concept of a public open online course and foreign experience in its application in the educational process, research on the current state of teaching computer graphics